Advanced methodologies and technologies in medicine and healthcare - Khosrow-Pour, Mehdi, 1951- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2019)
"This book provides emerging research on bioinformatics, medical ethics, and clinical science in modern applications and settings. While highlighting the challenges medical practitioners and healthcare professionals face when treating patients and striving to optimize their processes, the book shows how revolutionary technologies and methods are vastly improving how healthcare is implemented globally"--Provided by publisher.